Coupling between super-powerful nanosecond-duration radio pulses and the atmosphere and lower ionospheric plasma - Черногор, Л. Ф.; Милованов, Ю. Б.; Розуменко, В. Т. (Visnyk of V.N. Karazin Kharkiv National University, series “Radio Physics and Electronics”, 2017)
The results of numerical simulations of disturbances in the electron density and temperature arising in the atmosphere and lower ionospheric plasma from nanosecond duration radio pulses of varying super-powers are presented. An electric breakdown of the atmosphere is shown to occur when the pulse energy P  0.3 – 1 GW at the frequency f  10 GHz or when P  1 – 30 GW at f  1 GHz. In order to optimize the process of the breakdown, this power must be increased tens of times. It has been demonstrated that the electron density in the 30–60 km altitude range can be increased by 12 orders of magnitude. An increase in the electron temperature attains a factor of 10 – 100. The pulse durations and powers necessary for producing artificial ionized layers have been estimated.